Comparing Reading Performance Between Xitsonga as The Language of Instruction and as the Second Language (International Journal of Language, Literacy and Translation, 2025)
Background: As shown by the Progress in International Reading Study (PIRLS) findings over four successive cycles (2006, 2011, 2016, and 2021), South African Grade 4 learners’ performance in reading literacy is low, irrespective of the language in which reading is assessed. Xitsonga home language (HL) learners are assessed in Grade 4, but very little research on early reading development in this language has been undertaken.Objectives: This article aims to examine whether Xitsonga HL reading develops differently when it is used as the language of instruction compared to being used as the second language (L2).Method: The quantitative case study was conducted in five schools in the Mopani district of Limpopo Province. The early grade reading assessment (EGRA) instrument was adapted to Xitsonga, and 75 Grade 1s were selected in this study simply because Grade 1 is an important reading milestone children have to go through to help them cope with more advanced reading skills in higher grades.Results: The findings showed significant differences between Xitsonga HL and L2 in favour of L2. It was unexpected for Xitsonga HL learners to be outscored by learners who were taught Xitsonga as an L2, given that HL learners often use the language at home.Conclusion: Based on the findings, it is evident that teachers need to consider the orthographic nature of African languages when teaching reading in the Foundation Phase (Grades 1-3) classroom. Moreover, teaching reading requires an expert reading teacher who is familiar with the cultural, linguistic, and educational backgrounds of their learners. Thus, this requires teachers to be constantly professionally developed through suitable, accurate, and updated materials to help them improve their teaching of reading.